Supply Chain Geographic Information System Operation Model for Products Management for Logistics Industry in Thailand - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The research presents supply chain geographic information system operation model for products management for logistics industry in Thailand is composed of four main element, main suppliers The firm customers. The aim of this research to develop and to assess supply chain geographic information system operation model for products management for logistics industry in Thailand. A sample groups were five experts in supply chain, five experts in geographic information system . . Data analysis was the average mean and standard deviation. The results from experts agreement of supply chain geographic information system operation model for products management for logistics industry in Thailand was a high level. It showed that supply chain geographic information system operation model for products management for logistics industry in Thailand support sustainable development.